Conservação pós-colheita de batata-doce (ipomoea batatas l.) cultivada sob lâminas de irrigação - Araújo, Carla Sabrina Pereira de (Universidade Federal Rural do Semi-Árido, 2018)
Sweet potato (Ipomoea batatas L.) is the sixth most consumed vegetable in the world. Root quality can be influenced by the factors that precede the harvest, and by post-harvest factors. Thus, the objective of this work was to evaluate the post-harvest conservation of sweet potatoes cultivated under different irrigation regimes. For this, an experiment was carried out at Frutacor farm, located in the municipality of Russas, located 165 km from Fortaleza, Ceará (04°56'25'' S and 37°58'33'' W, 20 m altitude). The plants were cultivated under three irrigation regimes (80%, 100% and 120% ETc) and after 165 days, the roots were harvested, sanitized and stored in cold room (60 days, 20 ± 2 ° C, 80% RU). Each 15 days (0, 15, 30, 45 and 60 days after harvest), we evaluated: firmness, peel color (L, ° H, c *), dry matter, weight loss, pH, soluble solids, ratio, reducing sugars, starch and total phenolics. A randomized complete block design was used, with four replications, in a split plot design (regime in plots and storage times in subplot). Total phenolics, starch content and total soluble sugars were altered by both irrigation regimes and storage time. Total soluble sugars were higher in 80%; reducing sugars were higher in 100%. At the end of the storage, ratio, firmness, °Hue and starch content were higher, and soluble solids were smaller than at the harvest time. Weight loss, soluble solids and titratable acidity increased up to 15th day, and decreased until the end of the storage. The storage did not alter brightness and chroma, dry matter, pH and reducing sugars content. However, firmness, °Hue and the starch content decreased, and ratio increased, during the storage. The results showed that quality of sweet potato is influenced by the post-harvest storage and the supply of water applied to the plants during cultivation
Post-harvest conservation of sweet potato (ipomoea potatoes l.) cultivated under different irrigation regime
Keywords: Armazenamento pós-colheita; Convolvulaceae; Raízes tuberosas; Post-harvest storage; Convolvulaceae; Tubers; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA